2017
DOI: 10.3390/v9110315
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Newly Isolated Phages Belonging to PB1-Like, phiKZ-Like and LUZ24-Like Viruses against Multi-Drug Resistant Pseudomonas aeruginosa under Varying Growth Conditions

Abstract: In this study, we characterize three phages (SL1 SL2, and SL4), isolated from hospital sewage with lytic activity against clinical isolates of multi-drug resistant Pseudomonas aeruginosa (MDR-PA). The host spectrum ranged from 41% to 54%, with all three phages together covering 79% of all tested clinical isolates. Genome analysis revealed that SL1 (65,849 bp, 91 open reading frames ORFs) belongs to PB1-like viruses, SL2 (279,696 bp, 354 ORFs) to phiKZ-like viruses and SL4 (44,194 bp, 65 ORFs) to LUZ24-like vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 63 publications
5
41
3
2
Order By: Relevance
“…The genome of jumbo phage AR9 infecting B. subtilis , a close relative of the PBS2 phage, was sequenced and shown to contain genes orthologous to the RNAP genes of phiKZ-like phages [ 18 ], suggesting that the PBS2 RNAP purified a long time ago [ 35 , 36 ] in fact belongs to this new group of non-canonical jumbo phage RNAPs. At the time of this writing, several dozens of jumbo phages encoding distant homologs of the β′ and β subunits are known [ 18 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. They infect diverse bacterial hosts including members of Pseudomonas , Salmonella , Yersinia , Erwinia , Vibrio , Ralstonia , Bacillus , Aeromonas , Serratia , Klebsiella , Escherichia , and other genera [ 18 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , …”
Section: Jumbo Phages Encoding Rna Polymerases and Their Featuresmentioning
confidence: 99%
“…The genome of jumbo phage AR9 infecting B. subtilis , a close relative of the PBS2 phage, was sequenced and shown to contain genes orthologous to the RNAP genes of phiKZ-like phages [ 18 ], suggesting that the PBS2 RNAP purified a long time ago [ 35 , 36 ] in fact belongs to this new group of non-canonical jumbo phage RNAPs. At the time of this writing, several dozens of jumbo phages encoding distant homologs of the β′ and β subunits are known [ 18 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. They infect diverse bacterial hosts including members of Pseudomonas , Salmonella , Yersinia , Erwinia , Vibrio , Ralstonia , Bacillus , Aeromonas , Serratia , Klebsiella , Escherichia , and other genera [ 18 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , …”
Section: Jumbo Phages Encoding Rna Polymerases and Their Featuresmentioning
confidence: 99%
“…The characteristics of the Vibrio phage pVa-21 and its genome are expected to broaden the phiKZ-like phage library and help promote the application of bacteriophages in biofilm control to protect aquatic organisms from infection. In addition, as illustrated in a recent study [37], biofilm eradication by phiKZ-like phages in multidrug resistant bacteria suggests that the phiKZ-like phage, pVa-21, could also be used as a bio-control agent. The lytic effect of pVa-21 itself and the three distinct enzymes it possesses are expected to eradicate bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…No synergistic and no antagonistic effects of a cocktail was found with the three phages, however, the three-phage cocktail was as effective as the best phage alone. 96 Various studies demonstrated that different bacteriophages were able to reduce and lyse MDR P. aeruginosa in animal and in vitro conditions. 64,97,98 Additional animal studies show similarly promising results for MDR E. coli O25:H4-ST13, Vibrio parahaemolyticus, and S. aureus.…”
Section: Global Concern For Mdr Xdr and Pdr Pathogensmentioning
confidence: 99%